Pelatihan Guru Sekolah Minggu dalam Menggunakan Media Digital untuk Pembinaan Iman Anak di Gereja Lokal - Fictor S. Misssa; Edwer Y. Dethan; Yanto Tefa; Petrus Pareira; Angelita Meneses (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2021)
This community service project aims to enhance Sunday School teachers’ ability to use digital media as a tool for children’s faith formation in local churches. The rapid development of information technology requires churches to adapt their educational ministries, including children’s spiritual learning. The training was conducted at the Christian Evangelical Church in Timor (GMIT) Sion Noelbaki Congregation, involving 25 Sunday School teachers. The implementation methods included needs observation, interactive workshops, practical sessions on creating digital Bible content, and direct mentoring in using media such as spiritual videos, PowerPoint, and online platforms (YouTube, Canva, and WhatsApp Groups). Evaluation was carried out through pretest-posttest and participant satisfaction questionnaires. The results showed a 78% increase in teachers’ competence in using digital media after the training. Participants also demonstrated high enthusiasm and commitment to applying digital media in their children’s ministry. This activity had a positive impact on improving the quality of faith education, making Sunday School learning more engaging, contextual, and relevant to children’s lives in the digital era.